Too much of a good thing Mae West as cultural icon - Curry, Ramona, 1951- (Minneapolis : University of Minnesota Press, 1996)
Before Madonna, before Marilyn, there was Mae. The impact of Mae West - through her films, attitude, and aphorisms ("Too much of a good thing can be wonderful"; "Is that a gun in your pocket, or are you just glad to see me?") - continues to reverberate through American popular culture more than fifteen years after her death. In Too Much of a Good Thing, Ramona Curry examines the interplay between West's bawdy, worldly persona and twentieth-century gender and media politics.
Although West has remained an important figure, her image has fulfilled varied cultural functions. In the thirties, she was a lightning rod for debates over morality and censorship. In the seventies, the complexity of her portrayal of gender made her a controversial figure for both the gay rights and feminist movements.
Curry not only analyzes the symbolic roles West has occupied, arguing that the entertainer represents a carefully orchestrated transgression of race, class, and gender expectations, she also illustrates how icons of pop culture often distill contested social issues, serving diverse and even contradictory political functions.
A pithy and innovative look at what Mae West means, Too Much of a Good Thing is must reading for fans, film buffs, and anyone interested in how popular culture evolves and circulates in the United States.
Introduction: Posthumous Citings from Pistol to Puddle -- 1. The Sex "Queen" -- 2. The Prostitute, the Production Code, and the Depression -- 3. The Star Commodity from Asset to Liability -- 4. Comedic Performance from Social Satire to Self-Parody -- 5. The Female Impersonator in Gender Politics -- 6. Merging Interests.
Includes bibliographical references (p. 195-207) and index.
Keywords: West, Mae -- Criticism and interpretation